(untitled) (Biocenosis, 2026)
In Costa Rica, each citizen generates an average of 0.73 kilograms of waste per day, equivalent to 266 kilograms of garbage per year. In the Brunca Region, approximately 145 million tons of waste are discarded annually; however, only 4 % of the waste is reused (Quesada, 2025). In the canton of Golfito (Puntarenas, Costa Rica), this issue poses significant risks to public health, the environment, and economic and social development. The study takes place at the Carlos Manuel Vicente Castro Technical Professional High School (Golfito, Costa Rica). The objective of the research is to propose sustainable strategies from an environmental education perspective using a comprehensive approach aimed at strengthening post-consumer waste management and promoting a culture of sustainability, through the contribution of the University Community Service Project TC-749 Regenera. A mixed-methods approach was implemented, predominantly qualitative, with a descriptive scope. An instrument was designed and applied to analyze the habits, knowledge, and perceptions of students, as well as teaching and administrative staff, regarding post-consumer waste management. The results highlight the need to implement coordinated and participatory strategies to consolidate integrated waste management, as well as to promote responsible consumption practices.